اسلامی قوانین میں حدیث کا مقام و اہمیت: Place and Importance of Hadīth in Islamic Law (Al-Qamar, 2021)
Undoubtedly, the subject of history has been present in its importance in every era because people recognize that it is the inertia that connects their past achievements with the present and as a result they continue on the road of progress. This happens because if these past achievements are not connected with the present, then the lost things cannot become the foundation of the truth, because it is real, which is another name for progress and prosperity.
Keywords: Necessity of Hadith; Sunnah in religion; achievement; prosperity